"I'm not doing that." An in-depth examination of nonparticipation in mail-out bowel cancer screening programs. Issue 6 (22nd June 2019) - Goodwin, Belinda C; March, Sonja; Crawford-Williams, Fiona; Chambers, Suzanne K; Dunn, Jeff
Abstract : The framework proposed here promotes an iterative process for developing and testing digital behavior change interventions, aiming to maximize behavior and health outcomes improvement by incorporating faster and more frequent testing cycles. Abstract: Despite a clear association between the early detection of bowel cancer and increased survival, participation in mail-out screening programs is poor. Several key barriers to participation have been identified, yet research has failed to examine the specific cognitions, actions, and individual contexts from which barriers emerge. The purpose of the current study was to gain a detailed understanding of the actual experience of kit receipt from the perspective of nonparticipants including their opinion on interventions that may be effective in promoting participation. Demographic differences in reasons for nonparticipation are also examined. Opt-out data from a national program was analyzed to detect demographic differences in reasons for nonparticipation. Qualitative interviews were conducted in a sample of "at risk" nonparticipants. Thematic analysis was conducted using an inductive phenomenological approach. Older, higher SES, male and previously screened participants were more likely to provide a medical reason for opting out of participation. Four key themes emerged from interview data. The first reflected intention; whereby participants were either intenders (i.e., they planned to participate) or refusers. Subsequent themes reflected practicalities, emotional reactions, and necessity. Differences between intenders and refusers within these themes as well as opinions regarding interventions were identified. Interventions involving interactions with health professionals, autonomous decision making, and those which emphasize the positive outcomes of screening may encourage refusers to participate in mail-out bowel cancer screening programs. Messages that reinforce the importance of screening or provide a practical reminder may be more useful for intenders.